Synergistic Effects of Content Marketing and Influencers Marketing on the Formation of Brand Awareness and Purchase Interest of TikTok Shop Users (Cirebon City Case Study) - Izza, Ahmad Mudrikul; Ardiansyah, Muhammad Nur; Barkah, Fajar; Romdonny, Jefry (International Journal of Social Service and Research, 2024)
This research aims to investigate the synergistic influence between Content Marketing and Influencer Marketing on the formation of Brand Awareness and Purchase Interest of TikTok Shop users in Cirebon City. The aim is to analyze the impact of these two marketing strategies on brand awareness and purchase intention and to test their influence significantly. The research method uses a quantitative approach using research instruments and statistical analysis, especially with SPSS version 24. Samples were taken through non-probability sampling with purposive sampling criteria for respondents aged 17-30 years who are users of the TikTok application in the Cirebon area. Research variables include Content Marketing (X1), Influencer Marketing (X2), Brand Awareness (Y1), and Purchase Intention (Y2). The analysis results show that Content Marketing and Influencer Marketing have a significant influence on Brand Awareness and Purchase Interest, with a high R Square value indicating the influence of these variables on the outcome. In conclusion, this research found that Content Marketing and Influencer Marketing play an important role in forming brand awareness and interest in purchasing products on the TikTok Shop. Recommendations include strengthening content-based marketing strategies and collaboration with influencers, as well as paying attention to the relationship between Brand Awareness and Purchase Interest to improve sales performance through the TikTok Shop platform. This research can be the basis for further research regarding the influence of Content Marketing and Influencer Marketing in the context of digital marketing.